PLASTIC SURGERY IN HYPOSPADIAS PATIENTS IN SHARIA MAQASHID REVIEW - Fatahilah Fatahillah; Cecep Soleh Kurniawan; Abdurahman Raden Aji Haqqi; Azme Matali (IAIN Bone, 2021)
Recently, Indonesia has been shocked by the problem of hypospadias patients from a former athlete who is also a soldier in the Indonesian Armed Forces (TNI), second sergeant (serda) AM. Treatment for hypospadias patients is based on the type of disability the patient has. Most hypospadias problems require surgery. Surgery is performed by placing the urethra in the correct position, correcting a sunken penis, and repairing the skin around the urethral opening, as the doctor may need to use the foreskin to make corrections. The purpose of this study is to describe the meaning of hypospadias and plastic surgery for hypospadias patients at the level of maqasid sharia. The methodology in this study uses library methods. From the point of view of the problem being studied, this investigation uses an integrity, philosophical, systematic, and general approach to seek this truth and wisdom or the essence of inquiry. The nature of this investigation is descriptive-analytical. The analytical method used in this investigation is descriptive, comparative, and critical analysis. This study found that hypospadias is a congenital urethral abnormality in male children, which is usually accompanied by an abnormal curvature and size of the penis. The law of plastic surgery for hypospadias patients is permissible because it is included in the collection of protection of religion, mind, soul, lineage, and property as maqasid daruriyyat, which is intended to uphold worldly and hereafter benefits. Hopefully, the results of this investigation will enrich the intellectual treasures for Muslim individuals and the public regarding the law of plastic surgery for hypospadias patients.